Effects of Stamm gastrostomy on gastric emptying rate in rats - YEGEN, BERRAK; KIYAN, GÜRSU; BOZKURT, SÜHEYLA (KARGER, 2004)
Aim: Although frequency of gastroesophageal reflux (GER) increases after gastrostomy, the role of gastric emptying in GER has not been evaluated. In this study, we examined the effects of Stamm gastrostomy on gastric emptying rate in rats and whether Stamm gastrostomy induces GER or not. Methods: Sprague-Dawley rats were divided into three groups. Stamm gastrostomy was done in the first group (SG). Sham operation was carried out in group 2 and the 3rd group served as control. Gastric emptying was assessed using both liquid and solid meals in each group at postoperative 14th day. For solid meal emptying, after fasting of 16 h, the rats were fed for 3 h and gastric emptying rate was measured at the fifth hour. Methylcellulose was used for emptying of liquids and it was given after the animals were fasted for 16 h and gastric emptying rate was measured 30 min later. Histological evaluation for GER was performed in all groups. Results: GER was observed pathophysiologically in 5 of the 7 rats in SG group. Gastric emptying rates of liquid and solid meals were found to be similar in control, SG or sham groups. Conclusion: Surgical gastrostomy does not affect the gastric emptying of solid and liquid meals in rats. Other mechanisms should be considered in the development of GER observed following gastrostomy. Copyright (C) 2004 S. Karger AG, Basel.
Keywords: Stamm gastrostomy; gastroesophageal reflux; gastric emptying; PERCUTANEOUS ENDOSCOPIC GASTROSTOMY; LOWER ESOPHAGEAL SPHINCTER; GASTROESOPHAGEAL REFLUX; FEEDING GASTROSTOMY; TUBE GASTROSTOMY; CHILDREN; PRESSURE; EXPERIENCE